GRK4-mediated adiponectin receptor-1 phosphorylative desensitization as a novel mechanism of reduced renal sodium excretion in hypertension. Issue 18 (25th September 2020) - Zhang, Yan; Wang, Shaoxiong; Huang, Hefei; Zeng, Andi; Han, Yu; Zeng, Cindy; Zheng, Shuo; Ren, Hongmei; Wang, Yajing; Huang, Yu; Jose, Pedro A.; Ma, Xin-Liang; et al.
Abstract: Hypertensive patients have impaired sodium excretion. However, the mechanisms are incompletely understood. Despite the established association between obesity/excess adiposity and hypertension, whether and how adiponectin, one of the adipokines, contributes to impaired sodium excretion in hypertension has not been previously investigated. The current study tested the hypothesis that adiponectin promotes natriuresis and diuresis in the normotensive state. However, impaired adiponectin-mediated natriuresis and diuresis are involved in pathogenesis of hypertension. We found that sodium excretion was reduced in adiponectin knockout (Adipo −/− ) mice; intrarenal arterial infusion of adiponectin-induced natriuresis and diuresis in Wistar–Kyoto (WKY) rats. However, the natriuretic and diuretic effects of adiponectin were impaired in spontaneously hypertensive rats (SHRs), which were ascribed to the hyperphosphorylation of adiponectin receptor and subsequent uncoupling from Gαi. Inhibition of adiponectin receptor phosphorylation by a specific point mutation restored its coupling with Gαi and the adiponectin-mediated inhibition of Na + -K + -ATPase activity in renal proximal tubule (RPT) cells from SHRs. Finally, we identified G protein-coupled receptor kinase 4 (GRK4) as a mediator of adiponectin receptor hyperphosphorylation; mice transgenic for a hyperphosphorylating variant of GRK4 replicated the abnormal adiponectin function observed in SHRs, whereas down-regulation of GRK4 by renal ultrasound-directed small interfering RNA (siRNA) restored the adiponectin-mediated sodium excretion and reduced the blood pressure in SHRs. We conclude that the stimulatory effect of adiponectin on sodium excretion is impaired in hypertension, which is ascribed to the increased renal GRK4 expression and activity. Targeting GRK4 restores impaired adiponectin-mediated sodium excretion in hypertension, thus representing a novel strategy against hypertension.